The Effect of Leadership Effectiveness and School’s Culture on Teacher’s Job Satisfaction - Fitri, Riadin; Lian, Bukman; Rahman, Andi (Yayasan Sembilan Pemuda Indonesia, 2024)
Teacher’s satisfaction is an important factor affecting teacher performance. Teacher’s performance satisfaction is influenced by several factors, including school culture. Besides that, the effectiveness of the principal’s leadership is also very important. This study reveals the effect of leadership effectiveness and school culture on the job satisfaction of vocational school teachers in Prabumulih City. By using a quantitative research method with a measuring tool in the form of a questionnaire triangulated with the results of observations and documentation studies. Data were obtained from 209 respondents who came from private and state vocational school teachers in Prabumulih City. Data analysis was carried out descriptively and inferentially. Descriptive analysis shows that the range of norms for each variable is in the fairly good category. Inferential analysis using simple linear regression and multiple linear regression. The results of the analysis show the positive influence of the independent variables on the dependent variable. The conclusion of the study shows that there is an effect of the effectiveness of leadership and school culture on teacher job satisfaction.